Analysis of Village and City in the Concept Modern Education - Aulia Safitri (CV. ADIBA AISHA AMIRA, 2022)
Differences in attitudes and behavior reflect that rural and urban children have different passions in studying. City children with existing facilities in schools and in some areas have been provided with fast information with the existing media they are no longer interested in seeking knowledge. So education has a very important role in alleviating poverty, especially in rural communities, where access to education is very limited. In addition, awareness of the importance of getting education is still very much in rural communities. To achieve this, it is necessary to cooperate with related parties in equitable access to education for all communities, especially rural communities in the context of alleviating poverty and improving sustainable welfare. In order to minimize the gap between education in urban and rural areas in terms of quality and quantity, education harmony is needed such as: structuring local content, determining curriculum standards and textbooks, determining study hours, teacher appointment patterns, provisions for the number of students per class, teaching hours for teachers and others are determined equally